Glycemia Around Exercise in Adults with Type 1 Diabetes Using Automated and Nonautomated Insulin Delivery Pumps: A Switch Pilot Trial - Richard Bracken (Diabetes Technology & Therapeutics, 2023)
In an in-patient switch study, 10 adults with type 1 diabetes (T1D) performed 45 min of moderate-intensity exercise on 2 occasions: (1) when using their usual insulin pump (UP) and (2) after transitioning to automated insulin delivery (AID) treatment (MiniMed™ 780G). Consensus glucose management guidelines for performing exercise were applied. Plasma glucose concentrations measured over a 3-h monitoring period were stratified into time below range (TBR, <3.9 mmol/L), time in range (TIR, 3.9–10.0 mmol/L), and time above range (TAR, >10.0 mmol/L).Overall, TBR (UP: 11 ± 21 vs. AID: 3% ± 10%, P = 0.413), TIR (UP: 53 ± 27 vs. AID: 66% ± 39%, P = 0.320), and TAR (UP: 37 ± 34 vs. AID: 31% ± 41%, P = 0.604) were similar between arms. A proportionately low number of people experienced exercise-induced hypoglycemia (UP: n = 2 vs. AID: n = 1, P = 1.00).In conclusion, switching to AID therapy did not alter patterns of glycemia around sustained moderate-intensity exercise in adults with T1D.